Hubungan Antara Self-Esteem dan Self-Confidence Remaja Panti Asuhan di Kecamatan Lima Kaum - Hafizhah Al Husna; Ardimen .; Sisrazen .; Sri Putri Rahayu Z (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2022)
This study aims to determine the correlation between self-esteem and self-confidence of orphanage youth. This study uses a quantitative approach with correlational techniques to 73 adolescents who live in an orphanage in Lima Kaum District. This study uses two scales, namely the self-esteem scale from Coopersmith and the self-confidence scale from Lauster. Data analysis used statistical analysis with the help of SPSS Version 20 software. The results showed that self-esteem had a significant positive relationship with self-confidence with a correlation coefficient value of 0.084> 0.05. This means that the higher the self-esteem of adolescents, the higher the self-confidence of adolescents. On the other hand, the lower the self-esteem of the teenager, the lower the self-confidence of the teenager. Keywords: self-esteem;self-confidence;adolescents